Biotechnological Valorization of Food Marine Wastes: Microbial Productions on Peptones Obtained from Aquaculture By-Products - José Antonio Vázquez; Ana I. Durán; Araceli Menduíña; Margarita Nogueira (Biomolecules, 2020)
Based on a biotechnological strategy, in the present work several peptones are produced from the Alcalase hydrolysis (0.1–0.2% v/w, 56–64 °C, pH 8.27–8.98, 3 h) and thermal processing (105 °C, 60 min) of wastes generated from the industrial processing of turbot, salmon, trout, seabream and seabass. These peptones were included (in the range of 2.6–11 g/L of soluble protein) as main source of organic nitrogen (protein substrates) in low-cost media for the culture of lactic acid bacteria (LAB), marine probiotic bacteria (MPB) and ubiquitous Gram+ bacteria. In most cases, batch fermentations conducted in aquaculture peptone media led to the best growth, metabolic productions and yields. Nevertheless, no significant differences between aquaculture peptones and commercial media were generally observed. Kinetic parameters from a logistic equation and used for cultures modeling were applied with the purpose of comparing the bioproduction outcomes. In economical terms, the validity of the aquaculture peptones as substitutives of the peptones (meat extract, casitone, etc.) from commercial media was also compared. The decreasing of the costs for LAB bioproductions ranged between 3–4 times and the growth costs of MPB and Gram+ bacteria were improved more than 70 and 15 times, respectively, in relation to those found in control commercial media.